The Association of Laryngeal Position on Videolaryngoscopy and Time Taken to Intubate Using Spatial Point Pattern Analysis of Prospectively Collected Quality Assurance Data. (12th January 2022) - Miller, Matthew R.; Gemal, Hugo; Ware, Sandra; Hayes-Bradley, Clare
Abstract : BACKGROUND: During videolaryngoscopy (VL), the larynx appears within the defined area of the video screen, and its location can be measured as a point within this space. Spatial statistics offer methods to explore the relationship between location data and associated variables of interest. The aims of this study were to use spatial point pattern analysis to explore if the position of the larynx on VL is associated with longer times to intubate, increased risk of a needing >1 intubation attempt, or percentage of glottic opening. METHODS: Quality assurance data and clinical notes from all prehospital intubations using C-MAC Pocket Monitor with CMAC-4 blade (Karl Storz) from January 1, 2018, to July 31, 2020, were reviewed. We extracted 6 measurements corresponding to the time taken to obtain the initial and then best laryngeal view, time to manipulate a bougie, and time to place the endotracheal tube, as well a percentage of glottic opening and a number of intubation attempts. Larynx location was the middle of the base of glottis, in cm from the left and bottom on the C-MAC screen. Two plots were produced to summarize the base of glottis location and time to perform each time component of intubation. Next, a cross mark function and a maximum absolute deviation hypothesis test were performed to assess the null hypotheses that the spatial distributions were random. The association between glottis location and >1 intubation attempt was assessed by a spatial relative risk plot. RESULTS: Of 619 eligible intubations, 385 had a video for analysis. The following time variables had a nonrandom spatial distribution with a tendency for longer times when the larynx was off-center to the top or right of the screen: laryngoscope passing from teeth to glottis, glottis first view to best view of the larynx, time from bougie appearing to being placed in the cords, and overall time from teeth to endotracheal tube passing through cords. There was no increased relative risk for >1 intubation attempt. CONCLUSIONS: Spatial point pattern analysis identified a relationship between the position of the larynx during VL and prolonged intubation times. We did not find a relationship between larynx location and >1 attempt. Whether the location of the larynx on the screen is a marker for difficult VL or if optimizing the larynx position to the center of the screen improves intubation times would require further prospective studies.